NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU PEPELING JEUNG PANGGEUING KARYA KH ACENG ZAKARIA - Saefullah, Agus Susilo; Hidayat, Rahman (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2024)
This research aims to identify and analyze the values ​​of character education contained in the book